5-azacitidine reversing "spent" phase polycythemia vera back to proliferative phase and need for phlebotomy. (July 2020) - Lerner, Jaren; Michel, Miguel; Dasanu, Constantin A
Introduction: Polycythemia vera is a myeloproliferative neoplasm (MPN) characterized by increased red blood cell mass. The natural evolution of this MPN is to progress to an anemic/cytopenic phase also known as "spent" phase prior to transformation into an accelerated and/or an overt leukemic phase. Case Report: Herein, we describe a case of a patient with polycythemia vera transitioning though a "spent" phase to an MPN in accelerated phase (MPN-AP). The patient had anemia, thrombocytopenia, neutrophilia and increased blasts in the bone marrow. Management and outcome: Upon treatment with four cycles of 5-azacitidine, the patient's polycythemia vera reversed back to the proliferative phase. Serial phlebotomies were again required. Discussion: Reversal of a "spent" phase by 5-azacitidine back to a proliferative polycythemia vera phase requiring phlebotomies has not been previously reported in the scientific literature. We might witness similar cases in the literature in the future years, which could lead to yet another therapeutic indication of this important pharmacologic agent.